Effect of Immersion Time of Shallot Extract and Atonicon Seed Germination of Shallot - Bahrudin Bahrudin; Muhammad Ansar; Abdul Rahim Thaha (Universitas Tadulako, 2018)
The need for raw materials of fried onions derived from 'lembah palu Shallot tubers variety is high enough and can not be fulfilled, because the productivity is still low. This study aimed to find the type of plant growth regulator substances (PGR) with a long period of proper immersion to improve the germination of Shallot tuber. The research was conducted on Mei until June 2017 in Bulupontou Village, Sigi Regency. The study used two factorial Randomized Block Design (RBD). First factor of type RGS: (Z1) onion extract 100 g/l water, and (Z2) atonic 5 ml/l water. The second factor was long seed immersion in PGR: (T1)=30 min; (T2)=60 minutes; (T3)=90 minutes, and (T4)=120 minutes. Each treatment was represented 20 plants and repeated 3 times, so it was used 480 plants. The results showed that (i) red onion tubers soaked with Shallot extract 100 g/liter of water for 30-90 minutes yielded 100% Germinations, and tubers soaked in red onion extract for 30 minutes resulted in germination rate 31.3%/etmal, (ii) the type of growth regulator of shallot extract and atonic (PGR) effect was not significant on the germination of shallot; and (iii) the 30 minute long growth regulator immersion produced the highest hypothetical vigor index.